Desecration of female dead bodies: Considerations, Uses and Practices on the Female Dead Body in Art and Visual Culture - González Gea, Esther (Eikón / Imago, 2021)
Through art history and visual culture, we count on the presence of dead naked female bodies, usually emphasizing their youth and beauty. The considerations exercised over them differ much from those that male bodies deserve in the same context. Among them, the scientific curiosity, the eroticism or the attraction converge to justify the exhibition and the contemplation of such dead female bodies. At the same time, the literary imaginary has fed several myths regarding the power that those females defunct bodies processed over men, originating along time in the mass media, particularly in the film field. Another component that has to be taken into account is the proliferation of post mortem photographs in which women appear showing up their female attributes, historically associated with feminity as sweet virginal beings or as worthy pious women. To sum up, the dead female bodies have been symbolically desecrates up to nowadays.